تقييم السياسات العقارية للقطاع الفلاحي في الجزائر والحلول المقترحة لحل الإشكالية العقارية - عبـة, أ/ فريـد (Recherches économiques et managériales, 2016)
تهدف هذه الورقة البحثية إلى تقييم مختلف الإصلاحات العقارية التي شهدها القطاع الفلاحي، فلقد تعددت التشريعات التي تناولت تنظيم العلاقة بين الأرض والفلاح فيما يتعلق بالأراضي التابعة للأملاك الوطنية الخاصة، لأنها تقع في المناطق الخصبة للبلاد والتي تمثل 1/3 المساحة الصالحة للزراعة،  وهذا ما أدى إلى تعقيد الوضعية العقارية، وأبرزت ظاهرة عدم الاستقرار والاطمئنان لدى المستفيدين، وهذا ما أثر في عملية التنمية الفلاحية، بسبب عدم وضوح السياسات العقارية المنتهجة أوانحرافها في التطبيق الكلمات المفتاحية : القطاع الفلاحي في الجزائر، السياسات الفلاحية في الجزائر، السياسة العقارية، مشكل العقار الفلاحي. Résumé     This paper aims to various real estate reforms witnessed by the agricultural sector assessment has varied legislation that dealt with organizing the relationship between the Earth and the farmer with respect to land of their own national of property, because it is located in the fertile areas of the country, which represents one third (1/3) of SAU, and this is what led the complexity of the real estate situation, and highlighted the phenomenon of stability and confidence among the beneficiaries, and this is what the impact on the agricultural development process, due to the lack of clarity of real estate policies made known deviation in the application.       key words : agricultural sector in Algeria, agricultural policies in Algeria, real estate policy, the problem of agricultural property.